EXPLORING THE INFLUENCE OF SHAFI'I SCHOOL AND ITS CORRELATION IN THE PRACTICE OF TAHLIL MARRIAGE IN INDONESIA - Ilham Pratama, Nurul Fikri (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2024)
Tahlil marriage, a legal practice rooted in the Shafi’i school of jurisprudence, has been assimilated into customary law across several regions in Indonesia, including Aceh, Jambi, Bengkulu, and Lombok. The enduring influence of the Shafi’i school in Indonesia is attributed to its early introduction during the initial spread of Islam in the archipelago by Shafi’i scholars and preachers. This influence persists today, as seen in the prevalence of Islamic boarding schools that rely on classical Shafi’i fiqh texts as their core references. Among traditionalist communities, classical fiqh continues to guide societal practices such as worship, transactions, and marriage. Although tahlil marriage is not recognized as valid under Indonesia’s positive law, some customary laws influenced by Islamic principles uphold it as a solution to reconcile couples following the pronouncement of triple divorce (talak tiga) outside the formal judicial system. Using a qualitative, literature-based approach, this study examines the concentration of the Shafi’i school in Indonesia as a key factor contributing to the persistence of tahlil marriage practices in various regions.Key words:Tahlil marriage, Shafi’ijurisprudence, customary law, Indonesia.